Poaceae endémicas del Perú - La Torre, María Isabel (2006)
The Poaceae are represented in Peru by 157 genera and 750 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly herbs. Here we recognize 81 endemic species in 19 genera. Peru’s endemic grasses have been found in practically all recognized ecological regions, although the majority is found in the Dry and Humid Puna, High Andean and Mesoandean regions, from sea level to 5500 m elevation. Twenty-five endemics have been reported to occur in Peru’s protected areas.